Cytoreductive nephrectomy in the current treatment algorithm. (September 2019) - Kuusk, Teele; Szabados, Bernadett; Liu, Wing Kin; Powles, Thomas; Bex, Axel
The two recent prospective randomized trials CARMENA and SURTIME have changed the therapy paradigm of metastatic renal cell carcinoma. The CARMENA trial was conducted to investigate whether cytoreductive nephrectomy (CN) is required in the targeted therapy area, whereas SURTIME studied whether deferred CN in combination with sunitinib can be used to identify patients with inherent targeted therapy resistance. In the current review, we provide a comprehensive discussion of two randomized studies and the current evidence with up-do-date algorithms for treating primary metastatic clear-cell renal cell carcinoma in the era of targeted therapy and immune-checkpoint inhibition.